2022
DOI: 10.4012/dmj.2021-210
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties and biocompatibility of sandblasted and acid-etched titanium–zirconium binary alloys with various compositions

Abstract: Ti-Zr alloys have been investigated as an alternative to commercially pure Ti (c.p.Ti). According to our previous studies on the mechanical properties of Ti-Zr alloys, a Zr proportion in the range of 30-50 mol% has competitive advantages over Ti-10Zr and c.p.Ti. The aim of this study is to evaluate the biological response to Ti-Zr alloys with different compositions and their surface characteristics. Alloy surfaces are modified by sandblasting and sulfuric acid etching. As a result, similar surface structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The cell density was similar to that of Ti-15Mo-5Zr-3Al for Zr0 and Zr25 but decreased with an increasing Zr concentration. Similar to the results of this study, the addition of Zr has been reported to reduce the number of adherent cells [ 25 ]; however, the effect of Zr addition on cell density and cell viability remains inconsistent in the literature [ 26 ]. The cell behavior is largely dependent on the morphological, chemical (e.g., surface oxide composition and/or ion release), and physical (e.g., hardness) states of the surface [ 26 ].…”
Section: Resultssupporting
confidence: 85%
“…The cell density was similar to that of Ti-15Mo-5Zr-3Al for Zr0 and Zr25 but decreased with an increasing Zr concentration. Similar to the results of this study, the addition of Zr has been reported to reduce the number of adherent cells [ 25 ]; however, the effect of Zr addition on cell density and cell viability remains inconsistent in the literature [ 26 ]. The cell behavior is largely dependent on the morphological, chemical (e.g., surface oxide composition and/or ion release), and physical (e.g., hardness) states of the surface [ 26 ].…”
Section: Resultssupporting
confidence: 85%
“…% Zr had more Ca deposition than Ti-30 and 50at. %Zr on day 21 [39] . Therefore, these results may suggest that while Ti-50at.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade investigations on binary titanium alloys especially on the alloys with zirconium were in a continuous increase, leading to more knowledge about their use as alternative for antibacterial commercially pure Ti implant [2,25,30]. Especially for the dental applications, TiZr was found nowadays a good choice, having the mechanical and electrochemical stability properties in the case of a Zr proportion in the range of 30 -50 mol% with competitive merits over pure Ti [16,18,33]. An important problem related to biological response of TiZr alloys with both aspects such as biocompatibility and antibacterial effect was the subject of numerous papers [5,14,40] presenting coated and uncoated TiZr at micro and nanolevel.…”
Section: Introductionmentioning
confidence: 99%